The Dog as Observer and Witness of History [by the Novel of Viktoria Amelina Home for Dom - Polishchuk, Yaroslav; Pukhonska, Oksana (Poznańskie Studia Slawistyczne, 2021)
The authors of the article analyze one of the contemporary Ukrainian novels – Home for Dom (Дім для Дома, 2015) of Viktoria Amelina. Original feature of the plot is that protagonist and narrator of this work is dog Dom (Dominic). Writer, using an animalistic hero, has achieved not only a success between readers but she also has founded a new version for emotional rethinking of the past. The matter is that Viktoria Amelina tried to reveal the peculiarities of individual, family, city and national memory. Dog’s perception of the past in the novel is the author’s effort to replace accents from total estimates to relative and subtle ones. Different “faces” of memory is a value which writer shows in the examples of one Lviv family history. She combines all difficult and contradictory processes of the twentieth century – wars, genocides, repression, deportation, enslavement of man and people.